2018
DOI: 10.1093/mnras/sty2996
|View full text |Cite
|
Sign up to set email alerts
|

A SINFONI view of the nuclear activity and circumnuclear star formation in NGC 4303 – II. Spatially resolved stellar populations

Abstract: We present a spatially resolved stellar population study of the inner ∼200 pc radius of NGC 4303 based on near-infrared integral field spectroscopy with SINFONI/VLT at a spatial resolution of 40-80 pc and using the starlight code. We found the distribution of the stellar populations presents a spatial variation, suggesting an age stratification. Three main structures stand out. Two nuclear blobs, one composed by young stars (t ≤ 50 Myr) and one with intermediate-age stars (50 Myr < t ≤ 2 Gyr) both shifted from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 100 publications
(151 reference statements)
0
12
0
Order By: Relevance
“…These rings of young nuclear star formation associated with low velocity dispersions seem to be a common characteristic of local Seyfert galaxies as many studies using IFU data have found them within the central kpc (e.g. Riffel et al 2010Riffel et al , 2011Diniz et al 2017;Dametto et al 2019)…”
Section: The Circumnuclear Ringmentioning
confidence: 94%
“…These rings of young nuclear star formation associated with low velocity dispersions seem to be a common characteristic of local Seyfert galaxies as many studies using IFU data have found them within the central kpc (e.g. Riffel et al 2010Riffel et al , 2011Diniz et al 2017;Dametto et al 2019)…”
Section: The Circumnuclear Ringmentioning
confidence: 94%
“…Attempts to match the colors of large samples of galaxies from the near-ultraviolet (near-UV) to the near-IR have been found to leave significant residuals, sometimes leading authors to discard near-IR data in part of their analysis (Taylor et al 2011). Star formation histories derived from optical and near-IR data separately, or from a given data set with different population synthesis models, still differ significantly (Powalka et al 2017;Baldwin et al 2018;Dahmer-Hahn et al 2018;Dametto et al 2019;Riffel et al 2019). A part of the problem certainly lies in the theoretical modeling of advanced phases of stellar evolution, but it is also worth questioning the stellar spectral libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Most low-redshift disc galaxies host non-axisymmetric structures such as spiral arms and bars (Knapen et al 2000;Eskridge et al 2000;Masters et al 2011) which are likely to affect different stellar populations in different ways. It is known that azimuthal variation in the current star formation rate can arise as a result of the presence of bars (Martin & Friedli 1997;Verley et al 2007) and spiral arms (Gonzalez & Graham 1996;Puerari & Dottori 1997;Dametto et al 2019). Additionally, bars are associated with stable orbits (Contopoulos & Papayannopoulos 1980;Athanassoula 1992) and hence flattened stellar population gradients (Sánchez-Blázquez et al 2014, Fraser-McKelvie et al in prep.…”
Section: Introductionmentioning
confidence: 99%